The Effect of Expressive Writing Therapy on Fear Scores in Hospitalized Children Aged 10-12 Years - Susi Roida Simanjuntak; Selvin Tody; Milkha Pangalila; Khairun Nisa (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Introduction: Fear is one of the impacts of hospitalization commonly experienced by children. The fear experienced by children during hospitalization can contribute to the development of other psychological problems, therefore, nurses are expected to implement interventions to address children’s fear during hospitalization. This study aimed to analyze the effect of expressive writing on the level of fear among school-aged children undergoing hospitalization. Methods: The research design used in this study was a pre-experimental one-group pretest–posttest design involving 25 hospitalized children aged 10–12 years. The sampling technique used was purposive sampling. The instrument employed to measure children’s fear levels was the Children’s Fear Measurement Scale (CFS). The intervention implemented in this study was expressive writing administered over three days. Fear scores were measured on the first day prior to the intervention and re-measured on the third day after the intervention was completed. Data were analyzed using the Wilcoxon test. Results: The results showed that expressive writing therapy was significantly associated with fear scores (p < 0.05). This indicates that expressive writing therapy can help reduce fear scores in children after a three-day intervention. Conclusions: Based on these findings, expressive writing therapy can be considered as one of the nursing interventions to address fear in children during hospitalization. Nurses are expected to facilitate hospitalized children in engaging in expressive writing therapy.